Acellbia® and Mabtera® are recognize CD20-positive cells with equal efficiency - V. A. Misyurin; A. V. Misyurin; A. E. Misyurina; Yu. P. Finashutina; M. A. Baryshnikovа; O. S. Burova; S. K. Kravchenko (Онкогематология, 2015)
In present study were compared characteristics of rituximab produced by Hoffmann–La Roche (Mabtera®) and first domestic biosimilar Acellbia® from Biocad Company. Concentration of protein was measured using Bradford, s method. According to our results, protein concentration in formulations was the same. We electrophoresed formulations in denaturing conditions. Protein from formulations was denatured into fragments. Heavy and light chains of immunoglobulin were observed in gel. Finally, we performed flow cytometry where rituximab was used as primary antibody to detect CD20-positive B-cells of patients with B-cell chronic lymphocytic leukemia. Both Mabtera® and Acellbia® recognized the same number of cells. Thus, assays performed in vitro submitted identity of Mabtera® and Acellbia® characteristics.